Cultural Tourism 2013
DOI: 10.1079/9781845939236.0064
|View full text |Cite
|
Sign up to set email alerts
|

Mobile interpretation at cultural attractions: insights into users and non-users of audio-guides.

Abstract: This chapter deals with interpretation of heritage attractions. More specifically, it looks at mobile interpretation techniques, discusses their pros and cons, and presents findings from a study on the use of audio-guides conducted at a major museum in Vienna. The findings show that the majority of visitors used an audio-guide; however, there are also visitors who prefer conventional types of interpretation. The study also revealed that the use of an audio-guide does not lead to a greater depth of experience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Mobile tagging via quick response codes (QR codes) facilitates the combination of physical and virtual information. This technology can be applied for mobile tour guides, increasing interactivity, ticketing or online payment (Bauer-Kr€ osbacher, 2013).…”
Section: Potential Impact Of the Digital Divide On Cultural Tourismmentioning
confidence: 99%
“…Mobile tagging via quick response codes (QR codes) facilitates the combination of physical and virtual information. This technology can be applied for mobile tour guides, increasing interactivity, ticketing or online payment (Bauer-Kr€ osbacher, 2013).…”
Section: Potential Impact Of the Digital Divide On Cultural Tourismmentioning
confidence: 99%
“…There are many ways attractions can engage their visitors in the interpretation process (Bauer-Krösbacher, 2013;Lau & McKercher, 2007;Poria et al, 2009;Reisinger & Steiner, 2006). Some authors mention the importance of entertainment as a significant means for enabling the process (Light, 1995;Mitsche, Reino, Knox, & Bauernfeind, 2008;Timothy & Boyd, 2003), while others focus on interpretation provision that accounts for variables like socio-demographic characteristics.…”
Section: Heritage Interpretation Toolsmentioning
confidence: 99%
“…Once the visitor has been considered, the size of the site, the design, the message it wants to portray and the resources available are only a few factors that determine what interpretation media/tools can be employed (Binoy, 2011). Mitsche et al (2008) hone in on modern information technology as an important aspect of interpretation, while others have examined in depth the linkage between such technologies and meaningful experiences (Bauer-Krösbacher, 2013;Van Winkle & Backman, 2011). Mitsche et al (2008) hone in on modern information technology as an important aspect of interpretation, while others have examined in depth the linkage between such technologies and meaningful experiences (Bauer-Krösbacher, 2013;Van Winkle & Backman, 2011).…”
Section: Heritage Interpretation Toolsmentioning
confidence: 99%
“…As such, although visitors with sight can see a work of art, they may not know how to use that vision to look in ways that draw out its specific cultural or artistic significance, context, or meanings (Koide et al 2015;Vogt and Magnussen 2007). It has been recognised that interpretation can support the visitor in recognising significance and deriving meaning from an experience, and that without this support, fulfilment is likely to be low (Bauer-Krösbacher 2013). Some visitors may require more support than others.…”
Section: Introductionmentioning
confidence: 99%
“…This has historically led to concerns that audio tours can lock visitors into isolated experiential 'bubbles' (Aoki et al 2002). Other criticisms have been raised regarding audio guides and their isolating effect (Aoki et al 2002;Bauer-Krösbacher 2013;Lee 2017) and it has been suggested that they hamper the visitor's ability to enjoy the exhibits with full independence of thought (Bauer-Krösbacher 2013). Audio guides have also been criticised for being too detailed or distracting (Bauer-Krösbacher 2013).…”
Section: Introductionmentioning
confidence: 99%